Simple and robust current-mode maximum (MAX) circuit - Bütün, İsmail (Inst Engineering Technology-Iet, 2016)
A high-performance current-mode, multi-input winner-take-all maximum circuit is introduced. Owing to low-impedance low-capacitance input nodes involved, the speed of the new circuit is higher than major counterparts. Simulation results show that the new circuit exhibits superior performance compared with well-known rival counterparts in terms of speed, area, dynamic range and power dissipation.
Keywords: [No Keywords]